Rekonstruksi Pengaturan Tentang Suap Dan Gratifikasi Dalam Upaya Mewujudkan Kepastian Hukum - Slamet Wibowo (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Article 12B Paragraph (1) within the Law of Corruption Offenses bears resemblances to provisions regulating bribery offenses (Article 11, Article 12 letter a, letter b, and letter c), subsequently posing challenges in the implementation of law enforcement. Nonetheless, this article also demonstrates several advantages, including the introduction of the reversal of the burden of proof imposed on the defendant. In the effort to fortify the regulation pertaining to gratification offenses, reconstruction is required in several aspects. Firstly, the definition of gratification needs to be elaborated and clarified to avoid interpretation uncertainties. Secondly, the importance of mandatory reporting regulations concerning gratification receipts is crucial in realizing transparency in corruption prevention. Furthermore, precise gradation is needed regarding the elements of the articles and the threat of punishment for bribery and gratification offenses, including distinguishing between various types of gratification. To sustain effective law enforcement, it is recommended that the government evaluates Article 12B Paragraph (1) and undertakes reconstruction in accordance with the outlined suggestions. These steps are expected to address the regulatory overlaps between bribery and gratification, while strengthening the legal foundation to comprehensively combat corruption offenses.